Actinomycetes from bris soil and their secondary metabolities - Majhool, Ali Arkan (2020)
A total of 155 actinomycete strains were isolated from Beach Ridges Interspersed with Swales (BRIS)soils. Samples were collected at various depths from the earth surface and subsurface in Setiudistrict, Terengganu. The isolates were assessed for their antibacterial activity against apanel of microorganisms (Escherichia coli DSM30083T, Bacillus subtilis DSM10T, Pseudomonas fluorescens DSM 50090T, Klebsiella pneumoniae DSM30104T, Micrococcus luteus DSM20030T, and Saccharomyces cerevisiae). Results indicated that 65% of all isolates wereactive against, at least, one of the test organisms. Thirty-three of the isolates were selected andcharacterized by conventional methods and 16S rRNA gene sequence analysis revealed that most of theisolates belonged to the genus Streptomyces sp. (15 isolates) and 8 other rare genera namelyMicrotetrapora sp. (5 isolates), Streptacidiphilus sp. (3 isolates), Actinoplanes sp. (3 isolates),Microbispora sp. (2 isolates), Rothia sp. (1 isolate), Micromonospora sp. (2 isolates),Amycolatopsis sp. (1 isolate), and Sacharopolyspora sp. (1 isolate). Isolates that showedantibacterial activities were subjected to metabolite extraction and further analysis. Extractsexhibited a wide range of antimicrobial activities that varied with isolates and concentration ofeach extract. Thirty-nine compounds were detected both from Streptomyces sp. AA13 andAmycolatopsis sp. AA12, and thirty-eight compounds from Micromonospora sp. AA141, using GC-MS. Whole genome Sequence analysis conducted on isolate Amycolatopsis sp AA12produced a total of 5,304,429 paired-end reads and 51 potential secondary metabolitescoding gene clusters. Based on the analysis of metabolites from Amycolatopsis sp. (AA12) using NMRspectroscopy, the polyphenolic groups were isolated that including quercetin (C15H10O7), rutoside (C27H30O16), isotrifoliin (C21H20O12), and 3, 5, 6,7,3,4 heptahydroxyflavone. Most of the polyphenolic compounds exist as sugar conjugates. The biosynthesis ofdTDP-4-dehydrorhamnose 3, 5 -epimerase in Amycolatopsis sp. (AA12) is influenced by at least tengenes. The DTDP-sugars, derived from glucose 1-phosphate, are involved in the biosynthesis of polyphenolic compounds.